THE POTENTIAL OF PATIN FISH (Pangasius hypophthalmus) PROTEIN CONCENTRATE IN ADDRESSING OF STUNTING - Fitri, Samnil Astuti; Agustina, Fitratur Rahmah; Rahman, Defri (Literasi Kesehatan Husada: Jurnal Informasi Ilmu Kesehatan, 2024)
Background: Stunting has become a health problem in developing countries such as Indonesia. This can provide an effect on body composition, decreasing albumin levels and immunity status. Patin fish is well-known to have a high level of protein concentration and has a positive-effect on stunting. Objectives: The present study aimed to investigate the nutrient compound of Patin fish protein concentrate. Methods: The research method used is experimental laboratories. The test was carried out by Association of Official Agricultural Chemists method (AOAC) 2012. Results: The results showed that Patin Fish Protein Concentrate have high protein contain. A comprehensive literature review was conducted to gather scientific evidence regarding the effects of height protein intake on improving nutritional status, linear growth, and health outcomes in children with stunting. The literature review findings indicate that Patin Fish protein concentrate holds promise as a good protein source in enhancing the nutritional status and growth of stunting children. Additionally, Patin Fish protein concentrate may provide supplementary benefits in increasing intake of omega-3 fatty acids crucial for brain development and cognitive function in children. Conclusion: However, further experimental research is warranted to validate the findings of this literature review and assess the potential of Patin Fish protein concentrate in nutritional intervention programs for effectively addressing stunting.